P300/CBP Associated Factor (PCAF) Deficiency Enhances Diet-Induced Atherosclerosis in ApoE3*Leiden Mice via Systemic Inhibition of Regulatory T Cells - de Jong, Alwin; de Jong, Rob C. M.; Peters, Erna A.; Arens, Ramon; Jukema, J. Wouter; de Vries, Margreet R.; Quax, Paul H. A. (Frontiers in Cardiovascular Medicine, 2021)
Background: Inflammatory stimuli induced by NF-kB drive atherosclerotic lesion formation. The epigenetic P300/CBP associated factor (PCAF) post-transcriptionally acetylates Foxp3, which is required for regulatory T-cell (Treg) differentiation and immune modulation. We hypothesize that PCAF deficiency affects atherosclerosis via regulation of regulatory Tregs. Method: ApoE*3Leiden and ApoE*3LeidenxPCAF-/- (n=20) were fed a high-fat diet (HFD) containing 1% cholesterol. Systemic FoxP3+ T cells were measured every four weeks by flow cytometry. After five-months of HFD, mice were euthanized, and heart and blood were collected. IL-6 and TNFα concentrations were measured in plasma to identify systemic inflammatory responses. Compositional and morphometrical analyses were performed on the atherosclerotic lesions in the aortic sinuses. Results: After five months of HFD, plasma cholesterol concentrations were not different for ApoE*3LeidenxPCAF-/- compared to ApoE*3Leiden mice. Expression of FoxP3 by systemic CD4+ T cells decreased 1.8 fold in ApoE*3LeidenxPCAF-/- after five months HFD and remained significant reduced after five months of HFD. Systemic TNFα and IL-6 concentrations were comparable, whereas the atherosclerotic lesion size in ApoE*3LeidenxPCAF-/- mice was increased by 28% compared to ApoE*3Leiden mice. In atherosclerotic lesions, no differences were observed in macrophage differentiation or VSMC content, although a small increase in collagen was identified. Conclusion: Our data show that PCAF deficiency resulted in a decrease in circulatory FoxP3+ regulatory T cells and ameliorated atherosclerotic lesions with no differences in systemic inflammation or macrophage differentiation in the atherosclerotic lesions. This suggests that PCAF regulates atherosclerosis via modulation of Foxp3+ regulatory T-cell differentiation.